Revision surgery for failure of the dynamic stabilization system of the lumbar spine - V. E. Potapov; S. N. Larionov; A. P. Zhivotenko; A. V. Gorbunov; V. A. Sorokovikov (Acta Biomedica Scientifica, 2023)
The aim. To study the frequency and treatment options for dysfunction of the dynamic stabilization system of the lumbar spine. Materials and methods. We carried out a retrospective analysis of the treatment of 58  patients with degenerative pathology of the lumbar spine and instability of the spinal motion segments, who were treated at the neurosurgical unit of the Irkutsk Scientific Centre of Surgery and Traumatology in 2011–2020. The stability of spinal motion segment was assessed using X-ray imaging, magnetic resonance imaging and multi-layer spiral computed tomography of the lumbar spine. Revision surgery was performed in 7 out of 58 previously operated patients using the dynamic fixation system of spinal motion segments “Coflex” (Paradigm Spine LLC, Germany). Results. Revision surgery was performed in 7 out of 58 patients with dynamic fixation of the spinal motion segments with an interosseous implant due to an increase in pain syndrome. In 1 patient, the reason for repeated surgery was primary instability of the hardware caused by a fracture of the spinous process. In the delayed period, 4 patients had an X-ray picture with heterotopic ossification of the implant and instability of PDS. In two observations, a recurrence of intervertebral hernia was diagnosed at the level of the operated spinal motion segment. During revision surgery, a facetectomy was performed with stabilization by a peek cage, followed by pain management and clinical manifestation regression. Conclusion. The conducted study shows that a number of patients after discectomy and dynamic stabilization of the spine using “Coflex” system have inconsistency and  heterotypic ossification of  the implant and neoarthrosis. Implantation of a lumbar peek cage while maintaining the “Coflex” device makes it possible to form a rigid interbody fusion, which means it is sufficient and justified surgical technology for treating the failure of the dynamic stabilization system.